The architectural value of «La casa de Pilatos» in the Tradiciones peruanas by Ricardo Palma - Acosta Huamán, Francesca Tudela (2019)
This presentation will discuss the result of the research on «La Casa de Pilatos», text from Tradiciones peruanas, representative compendium of Ricardo Palma whose nickname was the «Bibliotecario Mendigo». We are particularly interested in highlighting the descriptive relationship of this building which has an architecture of the nineteenth century and a specific construction, and that also it is currently standing and functioning as the headquarters of the Constitutional Court of Peru. This essay will also analyze the considerations taken for «La Casa de Pilatos» to be considered as National Cultural Heritage since January 1973.